2008
DOI: 10.1097/icu.0b013e3282f4b1c2
|View full text |Cite
|
Sign up to set email alerts
|

New developments in scanning laser polarimetry for glaucoma

Abstract: With enhanced corneal compensation, the diagnostic accuracy of scanning laser polarimetry has been further improved for glaucoma. Newly developed algorithms for detecting any progressive retinal nerve fiber layer thinning await clinical validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…In glaucoma, several imaging devices are used to analyze the peripapillary RNFL thickness, 4,[18][19][20][21][22] and the reproducibility of the measurements is very important for diagnosis of the disease and monitoring of its progression. Several previous studies using Stratus OCT have addressed the reproducibility of RNFL thickness measurements in normal and glaucomatous eyes.…”
Section: Discussionmentioning
confidence: 99%
“…In glaucoma, several imaging devices are used to analyze the peripapillary RNFL thickness, 4,[18][19][20][21][22] and the reproducibility of the measurements is very important for diagnosis of the disease and monitoring of its progression. Several previous studies using Stratus OCT have addressed the reproducibility of RNFL thickness measurements in normal and glaucomatous eyes.…”
Section: Discussionmentioning
confidence: 99%
“…SLP devices compensate for the effect of this anterior segment birefringence with a special technique; in earlier devices with a fixed corneal compensator (FCC) and since 2002 using variable corneal compensation (VCC) as in current models like the GDx VCC (Carl Zeiss Meditec, Jena, Germany). The latest method, called enhanced corneal compensation (ECC), is said to have further improved the evaluation of the RNFL by the SLP device and, according to recent studies [4, 5] has increased both the diagnostic accuracy and the correlation between functional and structural measurements. Recent research indicates that there is still a large gap between the diagnostic conclusions reached using these modern imaging devices and the clinical assessment: a study of 312 glaucoma patients and 41 control participants by Pablo et al ., [6] found that the agreement between the stereophotographic evaluations and the conclusions based on SLT and SLP was just 52.9%.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever the observer of these images tries to assess whether obvious changes have occurred which may be interpreted as a sign of glaucomatous damage, it should be kept in mind that SLT does not measure the thickness of the retinal nerve fiber layer directly but rather puts its three-dimensional data in relation to a predetermined reference level. The measurements of both methods correlate with visual field loss in glaucoma patients [4, 8, 10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, the commercially available technology of scanning laser polarimetry uses retardation by RNFL birefringence as a measure of RNFL integrity [4]. The optical properties of the RNFL depend on axonal structure at the submicroscopic level; its birefringence, for example, arises from parallel intracellular fibrils called microtubules [5–8].…”
Section: Introductionmentioning
confidence: 99%